PENGARUH KARAKTERISTIK PERSONAL AUDITOR DAN TEKANAN ANGGARAN WAKTU TERHADAP PENERIMAAN PERILAKU DISFUNGSIONAL AUDIT (Studi Empiris pada Kantor Akuntan Publik di Wilayah Kota Malang) - Madinah Munnawaroh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The Head of Supervisory Board for Public Accounting Companies of the United States has announced to censure and impose civil penalty on Purwantoro, Suherman, and Surja audit firms and the partners of the Ernst and Young (EY) global network due to their involvement in the audit failure of PT Indosat Tbk Financial Statement in 2011 (PCAOB, 2017). The Indonesian member firm of EY global network has been assessed as having committed to dysfunctional audit behaviour, i.e. administering the audit steps too early without being supported by sufficient evidence. On the basis of such a consideration, it is important to carry out research on the dysfunctional audit behaviour.This research aims to identify the influence of auditors’ personal characteristics (locus of control, performance, organizational commitment, and turnover intention) and time budget pressure on the acceptance of dysfunctional audit behaviour. The research is conducted by survey method on the auditors working in the audit firm of Malang City. The samples are selected by convenience sampling technique, and it obtains 37 auditors. The data are analyzed using multiple linear regression method. The results show that organizational commitment, turnover intention, and time budget pressure significantly influence the acceptance of dysfunctional audit behaviour, while locus of control and performance do not affect the acceptance of dysfunctional audit behaviour.Keywords: Acceptance of dysfunctional audit behaviour, locus of control, performance, organizational commitment, turnover intention, time budget pressure.